A 3-hydroxythalidomide-based fluorescent probe for detection of fluoride in water sample and bioimaging in living cells. (March 2020) - Liu, Xiaolei; Yang, Zhen; Yang, Xiaofeng; Cui, Yu; Sun, Guoxin
Abstract: Thalidomide and its derivatives were drawing attentions as an old drug since the cereblon (CRBN) as a thalidomide-binding protein was identified. Herein, we reported its novel application in ion detection for the first time. And a turn-on fluorescent fluoride probe, (4-((tert-butyldimethylsilyl)oxy)-2-(2, 6-dioxopiperidin-3- yl)isoindoline-1, 3-dione was prepared using a protection-deprotection design strategy taking 3-hyroxythalidomide as parent compound. High selectivity and sensitivity for fluoride ion were observed with significant green fluorescent responses and a remarkable Stokes shift (about 178 nm). The fluorescent change was based on the exited state intramolecular proton transfer mechanism, which had been established by in-situ Fourier transform infrared spectroscopy and 1 H NMR techniques. In addition, the probe was successfully applied to detect the fluoride ion in lake water. More importantly, the probe was almost nontoxic to the cultured cells and was applied in bioimaging in living cells. Graphical abstract: Image 1 Highlights: The fluorescent properties of 3-hydroxythalidomide was firstly reported. We synthesized the first turn-on fluorescent probe (4-((tert-butyldimethylsilyl)oxy)-2-(2, 6-dioxopiperidin-3-yl)isoindoline-1, 3-dione, which was based on 3-hydroxythalidomide. This probe showed high selectivity and sensitivity for fluoride ion, and successfully applied in the detection of water sample and bioimaging in Hela cells. The in-situ FTIR technique was reported for the first time for revealing the sensing process.